Artificial intelligence applications using ChatGPT in education : case studies and practices - Aslam, Muhammad Shahzad; Nisar, Saima, 1988- (Hershey, PA : Information Science Reference, 2023)
'ChatGPT is recently introduce Artificial intelligence (AI) tool that uses large language model (LLM). It was developed by OpenAI and released in November 2022. Chatbots that use natural language AI, like ChatGPT, use enormous volumes of text data to anticipate words or phrases in a certain context. However, there is lack of knowledge on how to use such tool? What is the acceptability of AI tools in current era? What is the application of ChatGPT in medical education? How to use ChatGPT effectively and is there moral and ethical issues user faces when use ChatGPT?'--
Includes bibliographical references and index.
Keywords: ChatGPT; ChatGPT -- Case studies; Artificial intelligence -- Educational applications; Natural language generation (Computer science) -- Computer programs; Artificial intelligence -- Educational applications -- Case studies